Evaluacion comparativa de hibridos y variedades de arroz en los llanos centroccidentales de Venezuela - Alvarez, R.M.=700 1 Perez, M.; Reyes, E.; Moreno, O.J.; Delgado, N.
(Es, En)
ilus., 17 ref.
Keywords: ORYZA SATIVA; HIBRIDOS; VARIEDADES; VENEZUELA; AGRONOMIA TROPICAL